2017
DOI: 10.1038/s41598-017-03928-x
|View full text |Cite|
|
Sign up to set email alerts
|

Adenovirus-mediated suppression of hypothalamic glucokinase affects feeding behavior

Abstract: Glucokinase (GK), the hexokinase involved in glucosensing in pancreatic β-cells, is also expressed in arcuate nucleus (AN) neurons and hypothalamic tanycytes, the cells that surround the basal third ventricle (3V). Several lines of evidence suggest that tanycytes may be involved in the regulation of energy homeostasis. Tanycytes have extended cell processes that contact the feeding-regulating neurons in the AN, particularly, agouti-related protein (AgRP), neuropeptide Y (NPY), cocaine- and amphetamine-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 46 publications
6
37
0
2
Order By: Relevance
“…Thus, it is possible that the ependymal cells behave as a functional barrier to the adenovirus, preventing its entry into the subependymal zone, which is rich in astrocytes, and the parenchyma where neuroendocrine neurons are located. In contrast, using the same strategy (infection time and virus serotype), we have previously demonstrated that GK inhibitions in tanycytes increased food intake, meal duration, frequency of eating events and the cumulative eating time, whereas the intervals between meals were decreased, suggesting a decrease in satiety (Uranga et al, 2017). The present results indicate that inhibition of GLUT2 has an effect similar to inhibition of GK in vivo , suggesting that the mechanism of glucose detection requires both proteins, which supports the mechanism of indirect sensing involving tanycytes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, it is possible that the ependymal cells behave as a functional barrier to the adenovirus, preventing its entry into the subependymal zone, which is rich in astrocytes, and the parenchyma where neuroendocrine neurons are located. In contrast, using the same strategy (infection time and virus serotype), we have previously demonstrated that GK inhibitions in tanycytes increased food intake, meal duration, frequency of eating events and the cumulative eating time, whereas the intervals between meals were decreased, suggesting a decrease in satiety (Uranga et al, 2017). The present results indicate that inhibition of GLUT2 has an effect similar to inhibition of GK in vivo , suggesting that the mechanism of glucose detection requires both proteins, which supports the mechanism of indirect sensing involving tanycytes.…”
Section: Discussionmentioning
confidence: 96%
“…To evaluate the efficiency of in vivo transduction, we performed qRT-PCR and Western blot analysis at 48 hr postinfection. We have previously demonstrated that it is possible to detect changes in dietary behavior at this time point (Uranga et al, 2017). Rats were cannulated five days before the adenovirus injection into the 3V, and the hypothalamic tissues were collected after 48 hr, following the protocol shown in Figure 1a.…”
Section: In Vivo Ad-shglut2 Transductionmentioning
confidence: 99%
“…Using a similar approach, different laboratories developed viral constructs such as adenoviruses [18,44,45] and recombinant adeno-associated virus (rAAV) [14,46] to target tanycytes. As for CreERT2 mouse lines or TAT-Cre, these vectors have been first validated using fluorescent protein such as GFP [18,19,44,45] or tdTomato [14].…”
Section: Viral Modelmentioning
confidence: 99%
“…Using a similar approach, different laboratories developed viral constructs such as adenoviruses [18,44,45] and recombinant adeno-associated virus (rAAV) [14,46] to target tanycytes. As for CreERT2 mouse lines or TAT-Cre, these vectors have been first validated using fluorescent protein such as GFP [18,19,44,45] or tdTomato [14]. While adenoviruses efficiently target the ependymal layer in every ventricle without diffusing in the parenchyma [18,45], rAAV serotype has to be carefully chosen: indeed, some of them are more prone to target neurons such as AAV2 or AAV8, whereas others will target glial cells such as AAV4 or AAVDJ8 [47,48].…”
Section: Viral Modelmentioning
confidence: 99%
“…Uranga et al developed an adenovirus expressing GK shRNA to inhibit GK expression in tanycytes in vivo [28]. Their in vivo GK knockdown studies have revealed an increased food intake and altered feeding behavior.…”
Section: Glucose Homeostasis By Tanycytesmentioning
confidence: 99%